Keteladanan Kontekstual Peran Kepemimpinan Kepala Sekolah dalam Internalisasi Nilai Pancasila di SMK Rural - Ardyanti, Yuanita; Sulton, Sulton (Universitas Muhammadiyah Ponorogo, 2026)
This study intends to analyze the role and leadership strategies of school principals in maintaining and internalizing Pancasila values in vocational education, using qualitative research at SMKN 1 Badegan. The research approach used is qualitative with a phenomenological qualitative design. Data were collected through in-depth interviews with the principal, teachers, and students, participatory observation of learning activities, and analysis of curriculum documents and school policies. The results of the study indicated three main findings. First, value leadership was manifested primarily through the principal's direct modeling in school rituals and collaborative projects. Second, the internalization of values takes place contextually through integration into vocational practices such as teaching factories and project-based learning. Third, systemic challenges were found in the form of gaps in teachers' pedagogical capacity and the lack of adequate assessment instruments to objectively measure the internalization of values. This study concludes that value leadership in rural vocational schools requires a triadic approach that combines personal exemplary behavior, contextual curricular integration, and the strengthening of support systems such as teacher training and the development of authentic assessment rubrics. The implications of this study recommend capacity-building programs for school leaders and teachers, as well as the need to replicate studies in various vocational contexts to develop a more holistic model.